Negotiating treatment preferences: Physicians' formulations of patients' stance. (January 2016) - Landmark, Anne Marie Dalby; Svennevig, Jan; Gulbrandsen, Pål
Abstract: Eliciting patients' values and treatment preferences is an essential element in models of shared decision making, yet few studies have investigated the interactional realizations of how physicians do this in authentic encounters. Drawing on video-recorded encounters from Norwegian secondary care, the present study uses the fine-grained empirical methodology of conversation analysis (CA) to identify one conversational practice physicians use, namely, formulations of patients' stance, in which physicians summarize or paraphrase their understanding of the patient's stance towards treatment. The purpose of this study is twofold: (1) to explore what objectives formulations of patients' stance achieve while negotiating treatment and (2) to discuss these objectives in relation to core requirements in shared decision making. Our analysis demonstrates that formulating the patient's stance is a practice physicians use in order to elicit, check, and establish patients' attitudes towards treatment. This practice is in line with general recommendations for making shared decisions, such as exploring and checking patients' preferences and values. However, the formulations may function as a device for doing more than merely checking and establishing common ground and bringing up patients' preferences and views: Accompanied by subtle deprecating expressions, they work to delegitimize the patients' stances and indirectly convey the physicians' opposing stance. Once established, these positions can be used as a basis for challenging and potentially altering the patient's attitude towards the decision, thereby making it more congruent with the physician's view. Therefore, in addition to bringing up patients' views towards treatment, we argue that physicians may use formulations of patients' stance as a resource for directing the patient towards decisions that are congruent with the physician's stance in situations with potential disagreement, whilst (ostensibly) avoiding a more authoritarian or paternalistic approach. Highlights: Formulations of patients' stance (FPS) establish patients' treatment preferences. FPS can be used to elicit patients' rationale and challenge their position. FPS can implicitly convey the physicians' opposing stance. FPS can be used to influence the treatment decision. FPS may undermine the goals of shared decision making.